Penggunaan Media Camtasia Studio Berbantuan Handout untuk Meningkatkan Pemahaman Konsep Siswa pada Konsep Sistem Ekskresi di SMA Negeri 12 Banda Aceh - Dewi Mutia Maidani; Khairil Khairil; Hafnati Rahmatan (Biotik, 2016)
Camtasia studio media assisted handout is one of the learning resource that can be used by student as a substitute for textbook. The aim of this study was to find out students’ concept mastery of those who were taught by using camtasia studio media assisted handout and those who were taught by using conventional learning in the concept of excretion system. This study used experimental research that was implemented in SMA N 12 Banda Aceh in academic year 2014/2015. The subject of this study was 40 students, they were 20 students of IX IPA-2 and 20 students of IX IPA-3. The sample of study was 40 students, 20 students were chosen as the experimental group and 20 students as the control one. The data of students learning outcomes were taken from pretest and postest results. The N-Gain data of students’ learning outcomes were analyzed by using independent simple test and Kolmogorov-Smirnov test. There were three results of this study namely: the understanding of concept students was differed significantly between the students that taught by using Camtasia studio media assisted handout and the students taught conventionally with the value p = 0.000 < 0.05. It can be concluded that there was a significant differences in students’ concepts mastery between those who used Camtasia studio media assisted handout as the source of learning and those who received conventional learning in the concept of excretion system.